Closing county-level yield gaps through better phosphorus fertilizer management in Northeast China - Shi, Wuliang; Zhang, Yubin; Peng, Mengsu; Shi, Yang; Li, Wei; Liu, Pan; Li, Zheng; Song, Lixin; Cao, Ning; Cui, Jinhu; Cui, Zhenling (Frontiers in Environmental Science, 2022)
The limited available information on variations in yield gaps (differences between actual yields and the theoretically attainable yields) restricts the development of rational strategies to optimize yields and reduce environmental costs. Quantifying yield potential and the variations in yield gaps will help to identify factors that limit yields and will enable a narrowing of the current yield gap. Here, we applied an analytical framework to yield data to identify options for closing the yield gap at the county level. We used a database containing yields for 40 counties and data from 87 representative on-farm experiments in Jilin province, China, from 2006 to 2008. Yield potential was simulated for each region year using a Hybrid-Maize Model (http://www.hybridmaize.unl.edu/) and weather data. We then conducted a systematic and spatial analysis of actual yields to identify yield gaps at the county level. The simulated average potential yield at 27 representative sites was 15.2 Mg ha-1 (range 8.1 to 17.6 Mg ha-1) in Jilin province. The on-farm experiments suggested an attainable potential yield ranging from 8.7 to 16.7 Mg ha-1 across Jilin province. During this period, actual maize yield varied between 4.1 to 11.9 Mg ha-1 according to county level data. Farmers’ fields therefore achieved 52% of the model yield potential and 77% of the attainable potential yield. Widely different amounts of P fertilizer input among farmers’ contributed significantly to regional variations in the YGE. Soil Olsen-P and rainfall were also major factors. The results indicate that there is great potential to substantially increase maize yield in non-optimal P management regions, such as western Jilin Province. Our analyses s that there is great potential to substantially increase maize yield in non-optimal P management regions, such as the fields of western Jilin Province.